2004
DOI: 10.1002/jmv.20232
|View full text |Cite
|
Sign up to set email alerts
|

Early viral kinetics and treatment outcome in combination of high‐dose interferon induction vs. pegylated interferon plus ribavirin for naïve patients infected with hepatitis C virus of genotype 1b and high viral load

Abstract: An investigation was carried out to determine whether early viral monitoring could predict efficiently the virological response to combination therapy of two different regimens in treatment-naive chronic hepatitis C patients infected with genotype 1b with high baseline viral load. Patients were randomly assigned to receive interferon (IFN) alpha-2b induction (6 MU daily for 2 weeks) followed by 6 MU thrice weekly for 46 weeks (IFN/R group; n = 20), or pegylated IFN alpha-2b (1.5 microg/kg) weekly for 48 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 38 publications
3
52
1
Order By: Relevance
“…Early HCV dynamics may differ between patients receiving Peg-IFN and standard IFN [28] , because it takes 3 days before the maximum serum level is reached with Peg-IFN. In our previous study [29] , however, decreases in HCV RNA levels were significantly greater in patients with than without SVR from 24 h to 12 weeks after the start of combined Peg-IFN and ribavirin; they all were infected with HCV-1b in high loads. We have reported that polymorphisms of aa 70 and/or aa 91 in the core protein are associated with SVR in patients infected with HCV-1b in high loads ( 6 100 KIU/ ml) and useful in predicting response to Peg-IFN and ribavirin prior to the institution of therapy [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Early HCV dynamics may differ between patients receiving Peg-IFN and standard IFN [28] , because it takes 3 days before the maximum serum level is reached with Peg-IFN. In our previous study [29] , however, decreases in HCV RNA levels were significantly greater in patients with than without SVR from 24 h to 12 weeks after the start of combined Peg-IFN and ribavirin; they all were infected with HCV-1b in high loads. We have reported that polymorphisms of aa 70 and/or aa 91 in the core protein are associated with SVR in patients infected with HCV-1b in high loads ( 6 100 KIU/ ml) and useful in predicting response to Peg-IFN and ribavirin prior to the institution of therapy [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…At present, treatments based on interferon (IFN), in combination with ribavirin, are mainstay for combating HCV infection. In Japan, HCV genotype 1b (HCV-1b) in high viral loads (>100 kIU/ml) accounts for more than 70% of HCV infections, making it difficult to treat patients with chronic hepatitis C [3]. Such a background calls for efficient treatments of Japanese patients with chronic HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on Japanese patients infected with HCV-1b reported that IFN+RIB therapy increases the proportion of patients who achieve SVR [3,28] and that the incidence of HCC among patients who achieve SVR is lower than that among patients who do not [7]. In the present study, we examined the incidence and risk factors of HCC in HCV-1b patients who did not achieve SVR after IFN+RIB therapy.…”
Section: Discussionmentioning
confidence: 96%
“…At present, interferon (IFN), in combination with ribavirin (RIB), is the mainstay for treatment of HCV infection. In Japan, more than 70% of HCV infections are caused by HCV genotype 1b (HCV-1b) and are associated with a high viral load, making their treatment difficult [3]. …”
Section: Introductionmentioning
confidence: 99%